2007
DOI: 10.1002/chem.200600529
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Vinyl Ketone+OH and Methacrolein+OH Oxidation Reactions: A Master Equation Analysis of the Pressure‐ and Temperature‐Dependent Rate Constants

Abstract: High-level electronic structure calculations and master equation analyses were carried out to obtain the pressure- and temperature-dependent rate constants of the methyl vinyl ketone+OH and methacrolein+OH reactions. The balance between the OH addition reactions at the high-pressure limit, the OH addition reactions in the fall-off region, and the pressure-independent hydrogen abstractions involved in these multiwell and multichannel systems, has been shown to be crucial to understand the pressure and temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The energy of ap conformer is lower than that of the sp conformer by 3.5 kcal mol –1 at the HL level of theory, which is in consistent with the theoretical results performed by Ochando-Pardo et al, who obtained the ap : sp ratio of 99.6:0.4, and experimental results (97.5:2.5 and 100:0 at room temperature) also showed that the ap conformer of MACR has significant weight in its reactivity . So only the ap conformer was taken into account for the mechanism and kinetics study of the Cl + MACR reaction, just like researchers did with the OH + MACR reaction. , …”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The energy of ap conformer is lower than that of the sp conformer by 3.5 kcal mol –1 at the HL level of theory, which is in consistent with the theoretical results performed by Ochando-Pardo et al, who obtained the ap : sp ratio of 99.6:0.4, and experimental results (97.5:2.5 and 100:0 at room temperature) also showed that the ap conformer of MACR has significant weight in its reactivity . So only the ap conformer was taken into account for the mechanism and kinetics study of the Cl + MACR reaction, just like researchers did with the OH + MACR reaction. , …”
Section: Resultssupporting
confidence: 88%
“…47 So only the ap conformer was taken into account for the mechanism and kinetics study of the Cl + MACR reaction, just like researchers did with the OH + MACR reaction. 8,9 From the geometric structure of MACR shown in Figure 1, we can see that the Cl atom may react with MACR by the following possible paths: (1) addition, the Cl atom adds to the CC or the CO double bonds; (2) hydrogen atom abstraction, the Cl atom abstracts the aldehyde-H, the methyl-H, or the methylene-H atoms; (3) group abstraction, the Cl atom abstracts the −CH 3 or the −HCO group. In order to acquire the comprehensive reaction mechanism on which the kinetics calculation is based, we tried to calculate all of the above possible paths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, and according to a discussion by some of us, [65] this pressure dependence of a bimolecular reaction initiated by a recombination process like AD formation in the (R1ac) channel or RC formation in the indirect H-abstraction process is closely related to the depth of the well corresponding to the prereactive complex. In two competitive reactions, like (R1ac) and indirect H-abstraction, the probability of suffering deactivating collisions is higher for the adduct of the reaction with the deeper well and thus lower pressures are required to stabilize the adduct.…”
Section: Overall Dms + Oh Rate Constantmentioning
confidence: 89%
“…A number of studies have measured the reaction rate coefficient, k MVK+OH , over a wide range of pressure and temperature. ,, A negative temperature dependence was widely observed over a pressure range of 6–400 hPa. ,, Dependence of k MVK+OH on pressure at 2–7 hPa was both observed and predicted in the temperature range of 300–425 K. , The reported values of k MVK+OH in the high pressure limit at room temperature are in good agreement ∼2 × 10 –11 cm 3 molecule –1 s –1 ). Here, we use the IUPAC recommendation of k MVK+OH = (2.6 × 10 –12 )­e (610 K/ T ) cm 3 molecule –1 s –1 (Table ).…”
Section: Photochemistry Of Major Oxidation Products Of Isoprenementioning
confidence: 99%